Green Innovation, Green Intellectual Capital, and Organizational Green Culture on Competitive Advantage: Evidence from High-Profile Sector Companies in Indonesia - Dewi, R Rosiyana; Ananda, Salwa Utami (EQUITY, 2024)
This research aims to assess the effects of Green Innovation, Green Intellectual Capital, and Organizational Green Culture on Competitive Advantage. A quantitative approach is used, relying on secondary data. The sample consists of companies listed on the Indonesia Stock Exchange that have a high-profile status in sectors including energy, basic materials, industrials, consumer non-cyclical, consumer cyclical, and healthcare from 2020 to 2022. Purposive sampling was employed to select the sample. Over the last three years, 55 companies contributed to a total of 165 research samples. The study utilized panel data regression analysis with the help of Econometric Views (EVIEWS) 12 software. The results show that Green Innovation, Green Relational Capital, and Organizational Green Culture have a positive impact on Competitive Advantage. Conversely, Green Human Capital and Green Structural Capital did not have an effect on the company’s Competitive Advantage. Keywords: Competitive Advantage, Green Innovation, Green Intellectual Capital, Organizational Green Culture.